Evaluation of Piper nigrum L. as a Prebiotic Ingredient Using In Vitro Colon Model: Sarawak pepper as prebiotic ingredient - SITI MAISARAH MOHD NASHRI; HUI YAN TAN; SHAHRUL RAZID SARBINI (Borneo Journal of Resource Science and Technology, 2023)
Black and white pepper of the species Piper nigrum L. is regarded as the king of spices, and Malaysia is the second largest producer of peppercorns, after Indonesia. This spice contains abundant bioactive compounds that are capable of enhancing human health. However, the prebiotic potential of P. nigrum L. as a food ingredient has not yet been explored. Therefore, this research studied P. nigrum L. through in vitro gastrointestinal digestion and colonic fermentation using human faecal slurry. Samples were analysed for the colonic bacterial changes and its metabolites production using HPLC. Both black and white pepper showed prebiotic responses similar to those in inulin, particularly in stimulating the growth of human gastrointestinal microbiota. This study finds that P. nigrum L. promotes the growth of probiotic strains such as Bifidobacterium spp., and Lactobacillus / Enterococcus. Both black and white pepper also showed the ability to suppress colonic pathogen strain like Clostridium histolyticum. In vitro colonic fermentation of P. nigrum L. also significantly stimulate production of health beneficial metabolites. The production of short-chain fatty acids like acetate and propionate were observed to be particularly abundant. This is the contribution of piperine in both black and white pepper. In which, piperine provide both anti-bacterial and anti-inflammatory properties. Overall, P. nigrum L. showed appreciable prebiotic value similar to the commercial prebiotic, inulin. Thus, black and white pepper from Sarawak, Malaysia helps in promoting human gastrointestinal health. This finding may contribute to the value-added of Sarawak pepper as a functional food that can be involved in daily meals as spices.